2014
DOI: 10.1097/tp.0000000000000205
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric Dimethylarginine as Predictor of Graft loss and All-Cause Mortality in Renal Transplant Recipients

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
1
4
0
3
Order By: Relevance
“…However, SDMA level showed little correlation with levels of SCr, eGFR, BUN and UA in both HV and NB groups. Similar correlation coefficients were also uncovered by many reports, including meta-analysis and metabolomics studies 29 32 . Additionally, SDMA was reported to be independently associated with graft loss and mortality after adjusting for eGFR in human as well as in rodents 26 , 33 .…”
Section: Discussionsupporting
confidence: 82%
“…However, SDMA level showed little correlation with levels of SCr, eGFR, BUN and UA in both HV and NB groups. Similar correlation coefficients were also uncovered by many reports, including meta-analysis and metabolomics studies 29 32 . Additionally, SDMA was reported to be independently associated with graft loss and mortality after adjusting for eGFR in human as well as in rodents 26 , 33 .…”
Section: Discussionsupporting
confidence: 82%
“…[12] With respect to SDMA, initial studies did not find an association with adverse outcomes,[7, 13, 14] but some more recent studies reported positive associations with all-cause mortality or CVD. [11, 15, 16] Overall, prior studies on ADMA/SDMA and CVD or all-cause mortality were derived from many different study populations (general population,[15, 17, 18] patients with CVD,[9, 11, 19, 20] renal diseases,[7, 13, 2124] diabetes,[25, 26] or critically ill patients from intensive care unit,[2729] respectively), differed in their methodological approaches (e.g. using types of samples (plasma vs. serum) or methods to determine the biomarker levels (HPLC vs. tandem mass spectroscopy vs. ELISA), or considered different confounders in their analysis.…”
Section: Introductionmentioning
confidence: 99%
“…More novel markers such as asymmetric dimethylarginine, which is associated with endothelial dysfunction, are also associated with higher risk of mortality (HR = 2.18) and developing CVD (HR = 2.59) in ESRD [140] . Poorer graft outcomes are predicted by IL-6 [136,141] and elevated symmetric dimethylarginine [142] (HR = 5.51). TroponinT, usually used in the diagnosis of ACS, is a strong independent predictor of allcause mortality in stable RTRs [143] .…”
Section: Inflammationmentioning
confidence: 99%